The Status of the Customary Tenant In Relation To Land Held by Him under Customary Law: The Dilemma for the Conveyancers in Nigeria - Michael Takim Otu (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. The article seeks to examine the effects of the Land Use Act of 1978 on the customary system of land holding in Nigeria. Since the inception of the Act, the problem facing our courts, the unlearned public, and lawyers alike has been the determination of the true position of customary tenancy under the right of occupancy system introduced by the Act. In fact, the customary tenant is perplexed about the nature and scope of his property rights and obligations under the Act. These include his present duties and obligations, if any, to his customary overlord. The crux of the issue is whether he is to continue to pay the customary tribute to his overlord. Is he to continue seeking the approval or consent of the customary overlord before effecting a valid land transfer? Is he still under the spectre of forfeiture of his interests upon proof of bad behaviour against his overlord? Is the customary tenant entitled, as against his overlord, to the right of occupancy and the certificate of occupancy to be issued in evidence thereof? Thus, the controversy generated by these issues continues to defy consensus among the “egg heads” of our academia as well as the erudite judges of our courts. Indeed, many judicial decisions seem to demonstrate that the judiciary is yet to put the controversy on this issue to rest. As a result, the judicial quandary for Nigerian conveyancers continues to this day. Keywords: Customary Tenant, Overlord, Grantor, Grantee, Tribute, Rent, Forfeiture